Low molecular weight chitosan–protamine conjugate for siRNA delivery with enhanced stability and transfection efficiency. Issue 112 (22nd November 2016) - Patil, Sushilkumar; Bhatt, Priyanka; Lalani, Rohan; Amrutiya, Jitendra; Vhora, Imran; Kolte, Atul; Misra, Ambikanandan
Abstract : Chitosan is among the few polymers with high biocompatibility and low cytotoxicity. Abstract : Chitosan is among the few polymers with high biocompatibility and low toxicity. In the area of siRNA delivery, chitosan has been noted for its high buffer capacity in endosomal pH range. However, its applications are limited due to unfavorable physicochemical properties such as poor solubility, colloidal instability, unionized nature and weak binding with nucleic acids at physiologic pH which leads to premature release of nucleic acids, poor cell uptake and transfection. In order to overcome these limitations of chitosan, low molecular weight chitosan (LMWC) were prepared to improve its solubility and colloidal stability at physiologic pH. The obtained LMWC was conjugated with protamine to impart cationic charge and induce preferential binding with siRNA at physiologic pH. The polyplex were subjected to ionic cross-linking resulting in particle size of 143.7 nm and zeta potential of +12.8 mV. The polyplexes displayed enhanced resistance to displacement in heparin competition assay and to degradation in serum stability studies. Covalent conjugation also provided combined advantage of higher uptake due to cationic charge of protamine and endosomal escape capability of LMWC. The conjugate showed low cytotoxicity, high transfection efficiency and gene expression in vitro and were found safe in vivo .